Examination of Factors Influencing Capital Structure Decision: Evidence from Syria (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The study aims to explore the determinants of capital structure of Syrian joint stock companies, and to test whether the determinants offered by financial theory and previous studies are able to provide convincing explanations for companies in Syria. A total of 33 joint stock companies that subject to the supervision of Syrian Commission on Financial Markets and Securities were selected from year 2007 to 2011 (the period before the circumstances of Syrian crisis). This study applied eight determinants as independent variables: profitability, liquidity, business risk (volatility), growth prospects, tangibility, size, age, and taxes. On the other hand, the leverage ratio represented the variable related to the firm’s capital structure. To achieve the objective of the study, the researcher used a hypothetical-deductive approach to formulate the hypotheses, then in order to test these hypothesis, the researcher used panel data, which is a combination of data time series and cross section. The results found that there is a significant positive relationship between capital structure and the variables of profitability and size. Also, there is a significant negative relationship between capital structure and the variables of volatility; liquidity; and tangibility. While, there is no relationship with firm's age; expected growth; and taxes. يتمثل الهدف الرئيس لهذا البحث في استكشاف مُحددات هيكل رأس المال في الشّركات المُساهمة السّورية، واختبار فيما إذا كانت هذه المُحددات والمقترحة من خلال نظريات الهيكل المالي ونتائج الدِّراسات السّابقة تستطيع تقديم تفسير لقرار هيكل رأس المال في بيئة الأعمال السّورية. تتكون عينة البحث من 33 شّركة من الشركات المساهمة الخاضعة لإشراف هيئة الأوراق والأسواق المالية السّورية بالتّركيز على الفترة بين عاميّ 2007-2011 (الفترة قبل الأزمة السورية). ويتناول البحث دراسة العلاقة بين العوامل المُحددة لهيكل رأس المال مثل: الربحية؛ والسيولة؛ ومخاطر الأعمال؛ ومعدل النمو المتوقع؛ وهيكل الأصول؛ وحجم الشّركة؛ وعمر الشّركة؛ والضرائب (كمتغيرات مستقلة)، وبين نسبة المديونية كمقياس لهيكل رأس المال. ولتحقيق هدا الهدف، اعتمد الباحث على المدخل الاستنباطي لصياغة فرضيات البحث، ومن أجل اختبار هذه الفرضيات اعتمد الباحث على تحليل الانحدار الخطي البسيط باستخدام نموذج السّلسلة الزمنية المقطعية. أشارت نتائج الدّراسة إلى وجود علاقة إيجابية معنوية بين هيكل رأس المال للشركات المساهمة العامة السّورية وكل من حجم الشّركة؛ وربحيتها. ومن ناحية أخرى، أن العلاقة بين هيكل رأس المال، وكل من سيولة الشّركة؛ ومخاطرها؛ وهيكل أصولها؛ هي علاقة سلبية معنوية. أخيراً، لم تُقدم نتائج الدّراسة أية أدلة على وجود علاقة بين هيكل رأس المال وكل من عمر الشّركة؛ ومعدل النّمو المتوقع؛ ومعدل الضّريبة.